The Effectiveness of the Wordwall Media-Assisted Problem Based Learning Model on the Ability to Solve Problems in Science and Technology - Nuha, Farin Hanifatun; Wasino, Wasino; Widiarti, Nuni (Eduvest - Journal of Universal Studies, 2025)
This study aims to evaluate the effectiveness of the Problem Based Learning (PBL) learning model assisted by Wordwall media on the problem-solving ability and learning outcomes of students in science subjects in class V elementary school. Using a quantitative experimental design, the study involved two groups: experimental (Wordwall-assisted PBL) and control (media-free PBL). Data were collected through pre-test and post-test, with the results of the N-Gain analysis showing that the experimental group had an average effectiveness of 78.4% (effective category) compared to the control group’s 68.9% (moderately effective category). The T-Test showed significant differences between the two groups, supporting the superiority of Wordwall media use. This research confirms that Wordwall-assisted PBL not only improves problem-solving skills but also makes the learning process more engaging and interactive.